If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-2(3x-5)=-3x+1+15
We move all terms to the left:
3-2(3x-5)-(-3x+1+15)=0
We add all the numbers together, and all the variables
-2(3x-5)-(-3x+16)+3=0
We multiply parentheses
-6x-(-3x+16)+10+3=0
We get rid of parentheses
-6x+3x-16+10+3=0
We add all the numbers together, and all the variables
-3x-3=0
We move all terms containing x to the left, all other terms to the right
-3x=3
x=3/-3
x=-1
| r-5=15 | | 3n-18=9 | | 3x-9=5x-4+21-3 | | 6x+6=26x-91 | | -3.1x+7-7.4x=1.5x-6(x-32) | | 25+x-10=20 | | 7-3+12=x+6 | | 0/3r=2/1 | | –19t−–7t−6t+20t−–11=–15 | | 7x+12x=93 | | (2x-1)-69=90 | | 71+x=76 | | 0=-5x+15 | | 10(x-1)=2(x+15) | | 3x+60=-9x | | x+72+34=90 | | 6x-1)/4-(5-2x)/2=1 | | 7m+11=102 | | 8(v-3)=-72 | | 3x^2-21x=00 | | 2x=8x-24;X= | | x+2x+3x=4+7+1;X= | | 2a-(8a+1)-(a-2)×5=9 | | 0=x²-4 | | 18+p=26 | | 2√x-1=5 | | 8g+15=4g-29 | | 33m=8 | | x(x-8)=-10 | | 5x+15=-6x+14 | | 10z+30=10 | | 11x-2=6x+38 |